Analysis Astronomy Communication Actions in Brazil During the COVID-19 Pandemic - Penteado, Eduardo Monfardini; Spinelli, Patricia Figueiro; Silva do Nascimento, Willdson Robson [UNESP]; Lima, Gleici Kelly de [UNESP]; Nascimento, Josina Oliveira do; Carrelli, Felipe; Cortesi, Arianna (Int Astronomical Union, 2021)
In early 2020, the world was taken aback with the spread of the Covid-19 disease by an unknown coronavirus. Months later, the World Health Organization characterised this outbreak as a pandemic, urging decision makers to take actions to slow down the infection rate. Science communicators had to adapt their activities in support of recommendations for social distancing. In this article, we describe the mobilisation of astronomy communicators in Brazil, one of the most affected countries, as a consequence of social inequality, cuts in science funding and science denialism by the government. Practitioners filled out a survey, and the results showed that the amount and diversity of online activities increased considerably. Initiatives such as virtual exhibitions, transmission of sky observations and collective planetary sessions engaged thousands of people. Discussions about the pandemic and how science works were also present in several activities. The pandemic forced the community of astronomy communicators in Brazil to adapt to the situation, and motivated many of them to offer online activities. The diversity of those who communicate astronomy is extensive and appears to be increasing.
Keywords: astronomy communication; pandemic; virtual activities